Estudo de propriedades elétricas de nanotubos de carbono e monocamadas de ácido retinóico por microscopia de varredura por sonda - Karolline Aparecida de Souza Araujo (2016)
In this thesis, studies of transport mechanisms in single-walled carbon nanotubes (SWNT) and photo-assisted electrical response of Retinoic Acid (RA)s self-assembled monolayers on graphite are presented. Scanning Probe Microscopy (SPM) techniques along with Optical Spectroscopy (Photoluminescence and Raman) and theoretical calculations made possible the detailed study of the physical properties investigated. The charge transfer between neighboring single-walled carbon nanotubes (SWNTs) on a silicon oxide surface was investigated as a function of both the SWNT nature (metallic or semiconducting) and the anode/cathode distance. Morphological characterization, cutting and nanomanipulation of SWNTs was performed via Atomic Force Microscopy (AFM). The Electric Force Microscopy (EFM) measurements enabled the study of charge transfer. Two main mechanisms were observed: a direct electron tunneling described by the typical FowlerNordheim model, and indirect electron transfer (hopping) mediated by functional groups on the supporting surface. Both mechanisms depend on the SWNT nature and on the anode/cathode separation: direct electron tunneling dominates the charge transfer process for metallic SWNTs, especially for large distances, while both mechanisms compete with each other for semiconducting SWNTs, prevailing one over the other depending on the anode/cathode separation. The general phenomenological model proposed, that takes into account the two possible physical processes of charge transfer between the tubes, have adjusted in good agreement the experimental results. Finally, an important carotenoid was studied: RA is a semiconducting organic molecule optically active in the visible region with half of length of the famous carotenoid Beta-Carotene. A highly ordered RA self-assembled monolayer (SAM) on graphite was demonstrated. It was observed by AFM that the molecules are aligned parallel to the graphite with periodicity of 2.7nm. This in agreement with the results from study of the monolayer emission efficiency as a function of temperature. The EFM photo-assisted experiment suggested a graphite doping when decorated with molecules. This result was confirmed by Raman spectroscopy measurements that indicated a graphene p-type doping of the order of . The theoretical calculations performed corroborate the experimental results found.